Предмет: Алгебра,
автор: Alekseyiz
Найти производную функции y=e^3x tgx
Ответы
Автор ответа:
0
Ответ ответ ответ ответ ответ ответ ответ
Приложения:
Автор ответа:
0
y'=((e^3x)tgx)'=(e^3x)'tgx+(e^3x)(tgx)'
=(3x)'(e^3x)tgx+(e^3x)(tgx)'=
3(e^3x)tgx+(e^3x)(sinx/cosx)'=3(e^3x)tgx+
(e^3x)((sinx)'cosx-(cosx)'sinx)/((cosx)^2)=
3(e^3x)tgx+(e^3x)(cosxcosx-(-sin)sinx)/((cosx)^2)=
3(e^3x)tgx+(e^3x)((sinx)^2+(cosx)^2)/((cosx)^2)=
3(e^3x)tgx+(e^3x)(1/((cosx)^2))
=(3x)'(e^3x)tgx+(e^3x)(tgx)'=
3(e^3x)tgx+(e^3x)(sinx/cosx)'=3(e^3x)tgx+
(e^3x)((sinx)'cosx-(cosx)'sinx)/((cosx)^2)=
3(e^3x)tgx+(e^3x)(cosxcosx-(-sin)sinx)/((cosx)^2)=
3(e^3x)tgx+(e^3x)((sinx)^2+(cosx)^2)/((cosx)^2)=
3(e^3x)tgx+(e^3x)(1/((cosx)^2))
Приложения:
Похожие вопросы
Предмет: Информатика,
автор: darinaash
Предмет: Другие предметы,
автор: alsumu47
Предмет: Математика,
автор: rusakovnikolaj35
Предмет: Литература,
автор: dagaeva160